Decomposing transverse momentum balance contributions for quenched jets in PbPb collisions at s N N = 2.76 $$ \sqrt{s_{\mathrm{N}\;\mathrm{N}}}=2.76 $$ TeV - Cms, Collaboration; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; et al. (Springer Science and Business Media LLC, 2016)
Interactions between jets and the quark-gluon plasma produced in heavy ion collisions are studied via the angular distributions of summed charged-particle transverse momenta (pT) with respect to both the leading and subleading jet axes in high-pT dijet events. The contributions of charged particles in different momentum ranges to the overall event pT balance are decomposed into short-range jet peaks and a long-range azimuthal asymmetry in charged-particle pT. The results for PbPb collisions are compared to those in pp collisions using data collected in 2011 and 2013, at collision energy s NN =2.76 √sNN=2.76 TeV with integrated luminosities of 166 μb−1 and 5.3 pb−1, respectively, by the CMS experiment at the LHC. Measurements are presented as functions of PbPb collision centrality, charged-particle pT, relative azimuth, and radial distance from the jet axis for balanced and unbalanced dijets.
Keywords: Heavy Ion Experiments; Heavy-ion collision; Jet substructure; Quark gluon plasma; Compact Muon Solenoid; heavy ion: scattering; Temel Bilimler (SCI); Large Hadron Collider (LHC); High Energy Physics - Experiment; Heavy ion experiments; LHC; CMS; Quark-Gluon Plasma; PbPb; Centrality; Charged-particles; Physics, Particles & Fields; Temel Parçacıklar ve Alanlar; Heavy-ion collision; info:eu-repo/classification/ddc/530; Nuclear Experiment; quark gluon: plasma; Physical Sciences; CMS; Temel Bilimler; Physics; ddc:530; Physics, particles & fields; Jet Substructure; dijet; Nuclear & Particles Physics; Heavy ion experiments; Heavy-ion collision; Jet substructure; Quark gluon plasma; long-range; CERN LHC Coll; Natural Sciences (SCI); Physical Sciences; Heavy Ion Experiment; Physique des particules élémentaires; High energy physics, Experimental particle physics, LHC, CMS, Standard Model; Natural Sciences; Jet substructure; p p: scattering; Nuclear and High Energy Physics; angular distribution: asymmetry; Particles & Fields; short-range; Fizik; Quark gluon plasma; Physics; Heavy Ion Experiments; Heavy-İon Collision; Heavy Ion Experiments; Heavy-ion collision; Jet substructure; Quark gluon plasma; Heavy Ion Experiments; Heavy-ion collision; Jet substructure; Quark gluon plasma; Nuclear and High Energy Physics; Fizik, parçaciklar ve alanlar; ЭБ БГУ::ЕСТЕСТВЕННЫЕ И ТОЧНЫЕ НАУКИ::Физика; Mathematical Sciences; Science & Technology; momentum: difference; charged particle: transverse momentum; Basic Particles and Areas; Heavy Ion Experiments; Heavy-ion collision; Jet substructure; Quark gluon plasma; Nuclear Experiment; Nuclear Experiment; High Energy Physics - Experiment; Nuclear and High Energy Physics - LHC - CMS; Physics and Astronomy; QC Physics / fizika; jet: quenching; Quark Gluon Plasma